2020
DOI: 10.1111/jmwh.13131
|View full text |Cite
|
Sign up to set email alerts
|

The Health Care Provider's Role in Securing Work Accommodations for Pregnant and Postpartum Patients 

Abstract: Most women today are the primary, sole, or cobreadwinners for their families; their continued ability to work during and after pregnancy is crucial for their families’ well‐being. Midwives and other health care providers are regularly asked to provide work notes for patients who need adjustments to how, when, or where their job is done to continue working while maintaining a healthy pregnancy or breastfeeding. Whereas an improperly written work note can result in the patient being forced out on leave or losing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Franco et al found more than half of the pregnant workers in their cohort felt they needed accommodations, yet 40% of this population never requested them. 9 Without necessary, and in some cases legally protected, accommodations patients may be at increased risk for poor obstetrical outcomes. For example, a study examining the role of stress during pregnancy found increased levels of preterm birth were associated with a higher occupational fatigue score.…”
Section: Discussionmentioning
confidence: 99%
“…Franco et al found more than half of the pregnant workers in their cohort felt they needed accommodations, yet 40% of this population never requested them. 9 Without necessary, and in some cases legally protected, accommodations patients may be at increased risk for poor obstetrical outcomes. For example, a study examining the role of stress during pregnancy found increased levels of preterm birth were associated with a higher occupational fatigue score.…”
Section: Discussionmentioning
confidence: 99%